THE EFFECT OF THE STRATEGY OF SUMMARIZING IN ONLY THREE SENTENCES ON THE EXPRESSIVE PERFORMANCE OF FIFTH-GRADE PRIMARY SCHOOL STUDENTS - Saja Adel Ibrahim (Scholars Digest Publishing, 2024)
The current research was conducted in Iraq - Baghdad Governorate, and aimed to identify the effect of the strategy of summarizing in only three sentences on the expressive performance of fifth-grade primary school students in Baghdad Governorate for the academic year (2023-2024). The research sample reached (60) fifth-grade students. Primary school students at Al-Fath Primary School, and they were distributed into two equal groups (experimental and control) with (30) students in each group. The researcher rewarded the two groups statistically in the following variables (chronological age calculated in months, parents’ academic achievement, and Arabic language grades for the previous year), The research tool was a test to measure the expressive performance of the two research groups. The researcher used several statistical methods, including the t-test for two independent samples, the Pearson correlation coefficient, and the Chi-square. The researcher concluded that the students of the experimental group were superior to the students of the control group in expressive performance, and the result was that there were statistically significant differences. The average grades of the students of the two groups (experimental and control) were at a significance level (0.05) in favor of the experimental group that studied the expression using the summary strategy in only three sentences, thus rejecting the null hypothesis. Through that result, the researcher reached a number of recommendations and suggested conducting a study similar to the study. current.
Keywords: strategy of summarizing in only three sentences, expressive performance.